Efektivitas Video Edukasi Materi Perkalian Matriks - Sularsa; Ismail Rusli; Aprianti Putri Sujana (Journal of Technopreneurship and Information System (JTIS), 2023)
In learning, videos can help students understand material more easily. Especially if the video contains animations explaining abstract concepts. In this study, we conducted a survey to find out which subjects are considered the most difficult by students of SMK Teknologi Karawang. From the preliminary survey, we found that Mathematics is one of the most difficult subjects with matrix material being the most difficult material. For this reason, we created an example of an educational video to explain the concept of matrix multiplication through animation. To find out the effectiveness of the video that has been created, we conducted testing on 23 students. The 23 students were asked to do questions before and after watching the video. From the test results, it was found that the video increased the average student grade by 274%. Of course, these results cannot be generalized. Further testing is needed. For this reason, we plan to continue making videos of other materials and test them for a longer duration in the same place.